Contrast enhanced CT-scans are not comparable to non-enhanced scans in emphysema quantification - Heußel, Claus Peter; Kappes, Jutta; Finsterer, Romy; Hartlieb, Sissel; Weinheimer, O.; Kauczor, Hans-Ulrich; Eberhardt, Ralf (European journal of radiology, 2010)
Systemic, interventional and surgical treatments have gone new ways in treatment of emphysema. For longitudinal therapy monitoring and as end-points for clinical trials, quantification of the disease is necessary. Sensitive, easy to measure, as well as stable and reproducible parameters have to be characterized. One parameter that might affect emphysema quantification is IV contrast enhancement, which might also be indicated. Whether or not the contrast enhanced scan is also suited for emphysema quantification or an additional scan is necessary, a retrospective analysis of 12 adult patients undergoing clinically indicated both, a non-enhanced and enhanced thin section MSCT within a week (median 0 days, range 0-4 days) was done. The in-house YACTA software was used for automatic quantification of lung and emphysema volume, emphysema index, mean lung density, and 5th, 10th, 15th percentile. After IV contrast administration, the median CT derived lung volume decreased mild by 1.1%, while median emphysema volume decreased by relevant 11%. This results in a decrease of median emphysema index by 9%. The median lung density (15th percentile) increased after contrast application by 18 HU (9 HU). CT quantification delivers emphysema values that are clearly affected by IV contrast application. The detected changes after contrast application show the results of higher density in the lung parenchyma. Therefore the amount of quantified emphysema is reduced and the lung density increased after contrast enhancement. In longitudinal analyses, non-enhanced scans should be the reference, while enhanced scans cannot be used.
Gesehen am 10.05.2023